2018
DOI: 10.1080/10438599.2018.1557405
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and productivity in the food vs. the high-tech manufacturing sector

Abstract: The food sector is considered a mature and a research and development (R&D) extensive industry. Nevertheless, also food companies face numerous challenges and cannot abstain from innovation activity if they want to keep their competitive stance. We examine the impact of innovation on labor productivity in European food companies in comparison to results for firms operating in high-tech sectors. The central motivation of our study is that the observed low R&D intensity in the food sector should be mirrored in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…(Crepon, Duguet, and Mairessec 1998;Van Leeuwen and Klomp 2006;Roper, Du, and Love 2008;Mairesse and Jaumandreu 2005;Spiezia and Vivarelli 2002;Freeman and Soete 1987). Differences between high-tech and low-tech industries (Frick, Jantke, and Sauer 2019), and differences between fast-growing, stable, and declining firms, and the age of the firm (Coad, Segarra, and Teruel 2016) have been studied.…”
Section: Effects On Labour Productivitymentioning
confidence: 99%
“…(Crepon, Duguet, and Mairessec 1998;Van Leeuwen and Klomp 2006;Roper, Du, and Love 2008;Mairesse and Jaumandreu 2005;Spiezia and Vivarelli 2002;Freeman and Soete 1987). Differences between high-tech and low-tech industries (Frick, Jantke, and Sauer 2019), and differences between fast-growing, stable, and declining firms, and the age of the firm (Coad, Segarra, and Teruel 2016) have been studied.…”
Section: Effects On Labour Productivitymentioning
confidence: 99%
“…Subsequently, endogenous growth models suggest that production per unit of labour depends on the human capital, including training, education and investment on research and development (Romer, 1990). The empirical studies examining linkage between labour productivity and innovation were largely found to be positive (see, for instance, Apergis et al, 2008; Damanhouri & Rana, 2017; Frick et al, 2018; Lim & Sanida, 2011; Pianta & Vaona, 2007; Shafi’i & Ismail, 2015; Vuksic, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Though on the whole the aforementioned studies address the larger issue of determinants of labour productivity, especially innovation and labour productivity, these papers differ in their approach. For example, Frick et al (2018) examine the effect of innovation on labour productivity, considering the European food versus high-tech manufacturing sectors using the data of community innovation survey (CIS). Their results exhibit strong positive association between innovation and labour productivity in food sector, while it is insignificant in case of high-tech manufacturing sector.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is evident that firms in the food industry decide to innovate because they aim to satisfy consumers' needs and tastes and improve productivity (Cappellesso and Thomé, 2019; Cappellesso et al , 2020). They expect superior returns and – like all other kinds of firms – are profit maximisers (Pakes and Schankerman, 1984; Frick et al , 2019). Capital turnover is an objective indicator that perfectly fits with the measurement of achieved performance.…”
Section: Conceptual Framework Literature Review and Hypothesesmentioning
confidence: 99%
“…The first factor that firms can leverage is investments in R&D activities (Galizzi and Venturini, 1996; Leiponen, 2000; Avermaete et al , 2004; Frick et al , 2019). Despite the well-known uncertainty that characterises investments in R&D activities – firms do not know in advance if their investments and efforts in R&D activities will achieve results and if these results will be exploitable onto markets – firms need to realise these investments in order to develop their dynamic capabilities (Teece et al , 1997) and their absorptive capacity (Cohen and Levinthal, 1990).…”
Section: Conceptual Framework Literature Review and Hypothesesmentioning
confidence: 99%